Self-reported technological pedagogical content knowledge (TPACK) of pre-service teachers in relation to digital technology use in lesson plans - Schmid, Mirjam; Brianza, Eliana; Petko, Dominik (Computers in human behavior, 2021)
TPACK is a prominent model of teacher expertise for effectively teaching with digital technologies. While numerous studies have investigated teachers’ TPACK by means of self-report surveys, its relation to more objective outcomes like lesson planning has only recently come into focus. The aim of this study was to investigate whether differences in use of digital technologies in lesson plans are related to self-reported TPACK. Lesson plans of 173 pre-service teachers were coded for whether or not they included the use of digital technologies as well as for whether this use was intended for teachers or students. Independent t tests and ANOVAs were used to compare individual TPACK components among groups. Subsequently, unique profiles of all TPACK components were identified using cluster analyses and investigated for group differences via cross tabulation. Logistic and multinomial regressions were conducted to investigate the relations between TPACK profiles and technology use controlling for gender, age, and subject group. Overall results showed no significant group differences for either individual TPACK components or for the two- and five-cluster solutions of TPACK profiles. Subject group emerged as the only significant predictor and STEM pre-service teachers showed positive relations of TPACK components and technology use in lesson plans. •Self-reported TPACK is compared with coded technology use in lesson plans.•Different TPACK profiles emerge from clustering of subscales.•TPACK profiles are unrelated to technology use in lesson plans.•Differences in technology use found for subject groups, but not for gender or age.•STEM pre-service teachers showed positive relations of TPACK and technology use.